A comparative review of the outcomes of two different perinatal mortality classification systems at an Obstetric unit in Cape Town, South Africa - Siebritz, Mark (Stellenbosch : Stellenbosch University, 2012)
Thesis (MMed)--Stellenbosch University, 2012.